Uso de sistemas construídos de áreas alagadas (Constructed Wetland System - CWS) tipo ascendente/descendente, para tratamento de efluentes avícolas - Costa, Felipe Niero [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Human development and population growth during the twentieth century increased the water demand, tripling its consumption between 1950 and 1990. As the water streams were polluted; and as water is the source of minerals and also regulates vital functions, it becomes the vehicle of transmission and consequently spreads many diseases. Probably, the industries are the major responsible for this pollution when they dump untreated effluents to water streams, saturating the already insufficient net of sanitation facilities polluting water and soil. An effective treatment has been established with low cost in Europe and the United States, through constructed systems on wetlands Constructed Wetland Systems - CWSs, gradually used in other countries in the last three decades. Lately, we observe a continuous growth in Brazilian poultry business, and poultry industry showed greatest dynamism in the country, following the global market. Pondering this information and the efficiency of such treatment, this work aimed to study prototypes, in a laboratory scale, simulating ascending and descending types of CWSs, vegetated with aquatic macrophytes Eichhornia crassipes and the uses of aggregates and soil, to treat industrial wastewater from slaughterhouses and aviary. We conducted the initial characterization of the effluent to have an idea of its constituents and to scale the system and the continuous flow. Furthermore, we characterized the soil to be used in this system. The collects are periodically made in the refrigeration industry FRICOCK FRIGORIFICAÇÃO AVICULTURA INDÚSTRIA E COMÉRCIO LTDA. for local treatment simulation. The effluent that was treated with 12 prototypes of CWSs are analyzed with some frequency. The results of these reviews were compared to the effluent coming from the industry... (Complete abstract click electronic access below)

O desenvolvimento humano e o crescimento populacional durante o século XX fez com que a demanda de água aumentasse e muito, triplicando seu consumo entre 1950 e 1990. Com a poluição dos corpos hídricos, a água, fonte de sais minerais e reguladora de funções vitais, assume o papel de veículo de transmissão e disseminação de doenças. Provavelmente, as indústrias são uma das principais responsáveis por esta poluição quando lançam efluentes sem tratamento adequado aos corpos de águas, saturando a deficitária rede de saneamento básico e poluindo águas e solos. A conciliação de um tratamento eficiente e de baixo custo vem sendo estabelecida intensamente na Europa e Estados Unidos, por meio de sistemas construídos de áreas alagadas “Constructed Wetland Systems - CWSs”, utilizados gradativamente em outros países nas três últimas décadas. Ultimamente, se verifica um contínuo crescimento na atividade avícola brasileira, sendo que a avicultura de corte foi a que apresentou maior dinamismo no país, acompanhando o mercado mundial. Ponderando essas informações e a eficiência deste tipo de tratamento, este trabalho objetivou estudar protótipos, em escala laboratorial, simulando CWSs dos tipos ascendente e descendente, vegetados com macrófita aquática Eichhornia crassipes e uso de agregados e de solo, para tratamento de efluente industrial de matadouros e frigoríficos avícolas. Efetuou-se a caracterização inicial do efluente para se ter idéia de seus constituintes, bem como para dimensionar o sistema e o fluxo contínuo. Além disso, foi executada a caracterização do solo a ser usado no sistema. As coletas se deram periodicamente na indústria FRICOCK Frigorificação Avicultura Indústria e Comércio Ltda... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Resíduos; Nutrientes; Águas residuais - Purificação - Tratamento biológico; Wetlands